Teaching and research in teaching - Bernal Camacho, Germán (Universidad Pedagógica y Tecnológica de Colombia, 2003)
From a critical point of view, it contributes to the discussion on new "alternatives in the teaching of law", which go beyond the traditional scheme, not only of teaching it but also of understanding it. The way it has been taught is reviewed and elements are proposed that go beyond not only teaching but also the conception of traditional law and the professional formed in the hegemony of the static conception of Roman law and of other families of the Western legal system, which has prioritized in our case, more compliance with the law than law as a social science. A law inspired by a dynamic theory of learning as the creation of knowledge is proposed, with a nomadic pedagogy that links the legal to the social, political and economic reality of the environment where it moves, promoting processes of change and regional development. This implies, in addition to reflecting on the type of professional in the 21st century and the new content of law, promoting a change, where the law teacher is a researcher, who teaches how to produce condiment and not just consume it.